2020
DOI: 10.1021/acssynbio.0c00152
|View full text |Cite
|
Sign up to set email alerts
|

A Library of Tunable, Portable, and Inducer-Free Promoters Derived from Cyanobacteria

Abstract: Cyanobacteria are emerging as hosts for various biotechnological applications. The ability to engineer these photosynthetic prokaryotes greatly depends on the availability of well-characterized promoters. Inducer-free promoters of a range of activities may be desirable for the eventual large-scale, outdoor cultivations. Further, several native promoters of cyanobacteria are repressed by high carbon dioxide or light, and it would be of interest to alter this property. We started with PrbcL and PcpcB, the well-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Among the promoters tested, P cpcB560 had the strongest effect, in agreement with its super-strong activity due to the presence of multiple TFBS in its sequence (Zhou et al, 2014). This is in spite of previous reports that P cpcB is inhibited under strong light conditions (Sengupta et al, 2020a). The strong and continuous illumination was chosen in our study because previous studies, including our own preliminary studies, have shown that it leads to higher biomass accumulation for the WT PCC 7002 cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Among the promoters tested, P cpcB560 had the strongest effect, in agreement with its super-strong activity due to the presence of multiple TFBS in its sequence (Zhou et al, 2014). This is in spite of previous reports that P cpcB is inhibited under strong light conditions (Sengupta et al, 2020a). The strong and continuous illumination was chosen in our study because previous studies, including our own preliminary studies, have shown that it leads to higher biomass accumulation for the WT PCC 7002 cells.…”
Section: Discussionsupporting
confidence: 69%
“…P rbcL2A had a slightly lesser effect on SbtA expression, growth and glycogen accumulation compared to the P cpcB promoters. Our study shows that even under air bubbling and high illumination, very similar to the "optimal" conditions for high P rbcL activity (Sengupta et al, 2020a) P cpcB560 has higher activity compared to PrbcL2A. Promoter activity may also be affected by the length of the promoter chosen.…”
Section: Discussionmentioning
confidence: 56%
“…PCC 6803 [141,142]. Recently, a mutant promoter library from two popular promoters, P psbA and P cpc of S. elongatus PCC 7942, were generated to achieve promoters of varying strength [143]. A collection of 48 unique promoters were validated in three additional S. elongatus strains, expanding the cyanobacterial synthetic biology toolbox.…”
Section: Synthetic Biologymentioning
confidence: 99%
“…But clearly, integrating such a library on all the chromosomes of a polyploid microorganism is a major challenge, without going through the regular time-consuming segregation steps for a limited number of representatives. 7 How can one ensure that the genomic library integrated on the chromosomes of polyploid microorganisms is fully segregated? In other words, how can one ensure that all existing copies of the chromosome contain the intended fragment?…”
mentioning
confidence: 99%
“…Our work marks the first report of construction of a fully segregated chromosomal genomic library in polyploid microorganisms, without going through the time-consuming segregation step of only a small number of representatives. 7 This library could in principle be exploited either for fundamental research ( e.g. , detailing complex phenotypes) or synthetic biology applications ( e.g.…”
mentioning
confidence: 99%